Early‐onset venous thromboembolisms in newly diagnosed non‐promyelocytic acute myeloid leukemia patients undergoing intensive induction chemotherapy. (12th January 2023) - Koschade, Sebastian E.; Stratmann, Jan A.; Steffen, Björn; Shaid, Shabnam; Finkelmeier, Fabian; Serve, Hubert; Miesbach, Wolfgang; Brandts, Christian H.; Ballo, Olivier
Abstract: Objectives and Methods: Venous thromboembolic (VTE) events are emerging as frequent complications in acute myeloid leukemia (AML); however, there is insufficient data regarding epidemiology, risk factors, and impact on outcomes. The optimal approach to balance risks of thrombosis and hemorrhage remains unclear. This retrospective single‐center study in AML patients undergoing induction chemotherapy between 2007 and 2018 assessed incidence, risk factors, features, and outcomes of early‐onset VTE. Results: 423 patients (median age 59 years) were enrolled. VTE was diagnosed in 31 patients (7.3%) within 3 months of admission. The median time to VTE was 3 days. Non‐central venous catheter (CVC)‐related VTE occurred in 19 patients (61%). Main risk factor for VTE was leukocytosis at admission, independent of platelet counts/INR. Four patients (13%) exhibited VTE recurrence. No deaths directly related to VTE or major bleeding events associated with platelet‐adjusted anticoagulation in patients with VTE were recorded. There was no clear impact of VTE on 1‐year overall survival; however, non‐CVC‐related VTE may be associated with adverse outcomes. Conclusions: Early‐onset VTE is a common complication in newly diagnosed AML patients admitted for induction chemotherapy. Leukocytosis is an independent VTE risk factor. The potentially adverse impact of non‐CVC‐related VTE merits further study.